Asia redux : conceptualizing a region for our times ([s.l.] : Institute of Southeast Asian Studies, 2013)
'In the erudite essay that opens this forum, Prasenjit Duara turns to both indigenous thinkers and the premodern past for tools with which to think about Asia in a global age. Contemporary modalities of regional exchange -'weakly bounded, network-oriented, pluralistic, multitemporal' - chime with earlier patterns of cultural circulation without state domination, giving rise to a prophetic vision of'Asia Redux'. This attempt to capture the contours of a (re)-emergent region was calculated to provide. And what a debate it kicks off. Wang Hui resolutely reframe imagining Asia as a political project on a world-historical canvas. Tansen Sen greatly complicates the map of intra-Asian commercial exchange in earlier times; Amitav Acharya outlines five competing conceptions of Asia in the domain of international relations alone.; Barbara Watson Andaya teases out the paradoxical way in which regional religions make clashing claims about Asian unity; and Rudolf Mrazek asks, what of the Asia that bleeds? what of exploitation and its spawn, the inglorious'built-ends' of the global economy? The reward for those who read this collection straight through is a thrillingly cacophonous conversation about how to grasp Asia in our time.3 Karen E. Wigen, Stanford University.
Keywords: Regionalism -- Asia